G1 Executive task performance and anxiety are associated with self-awareness of neuropsychiatric symptoms in huntington's disease. (13th September 2016) - Andrews, Sophie C; Craufurd, David; Tabrizi, Sarah; Stout, Julie C; ,
Abstract : Background: Reduced self-awareness of neuropsychiatric symptoms is common in HD, but it is not clear how this awareness differs across disease stage, and the relative associations of clinical or cognitive correlates. Aims: We examined self-awareness of neuropsychiatric symptoms (executive function, apathy and disinhibition) in pre-manifest and early manifest HD, and assessed the extent to which awareness was associated with motor, cognitive and mood symptoms. Methods: 132 gene-positive participants (60 pre-manifest and 72 early diagnosed) were included from the multicentre TRACK-HD study. Participants and their informants completed self- and informant-versions of the Frontal Systems Behaviour Scale (FrSBe), and the discrepancy between self- and informant-reports was compared across pre-manifest and early HD groups as a measure of self-awareness. Participants' motor scores, Hospital Anxiety and Depression Scale scores, and performance on a composite of executive tasks (Trailmaking Test, Spot the Change Test, Symbol Digit Modalities Test) were assessed as predictors of self-awareness. Results: On the FrSBe, pre-manifest participants reported more executive dysfunction, apathy and disinhibition compared to their informants, whereas early HD participants reported less executive dysfunction and apathy than their informants, suggesting that self-awareness reduces as the disease progresses. Better performance on the executive composite was associated with higher self-awareness of executive dysfunction and apathy, and more self-reported anxiety was associated with self-awareness of apathy. Conclusions: Self-awareness of neuropsychiatric symptoms in HD is related to executive task performance and self-reported anxiety, rather than general disease progression, at least for pre-manifest and early diagnosed individuals. Clinicians should consider the impact that cognitive impairment and anxiety have on patients' awareness of their own neuropsychiatric symptoms.